A freshwater mesocosm study into the effects of the neonicotinoid insecticide thiamethoxam at multiple trophic levels. (November 2018) - Finnegan, Meaghean C.; Emburey, Simon; Hommen, Udo; Baxter, Leilan R.; Hoekstra, Paul F.; Hanson, Mark L.; Thompson, Helen; Hamer, Mick
Abstract: Thiamethoxam is a neonicotinoid insecticide used widely in agriculture to control a broad spectrum of insect pests. To assess potential risks from this compound to non-target aquatic organisms, an outdoor mesocosm study was performed. Mesocosms (1300 L) were treated once with a formulated product with the active substance (a.s.) thiamethoxam at nominal concentrations of 1 (n = 3), 3 (n = 3), 10 (n = 4), 30 (n = 4), and 100 (n = 2) μg a.s./L, plus untreated controls (n = 4). Primary producers (phytoplankton), zooplankton, and macroinvertebrates were monitored for up to 93 days following treatment. Thiamethoxam was observed to have a water column dissipation half-life (DT50) of ≤1.6–5.2 days in the mesocosms. Community-based principal response curve analysis detected no treatment effects for phytoplankton, zooplankton, emergent insects, and macroinvertebrates, indicating a lack of direct and indirect effects. A number of statistically significant differences from controls were detected for individual phytoplankton and zooplankton species abundances, but these were not considered to be treatment-related due to their transient nature and lack of concentration-response. After application of 30 μg a.s./L, slight temporary effects on Asellus aquaticus could not be excluded. At 100 μg a.s./L, there was an effect with no clear recovery of Asellus observed, likely due to their inability to recolonize these isolated test systems. A statistically significant but transient reduction in the emergence of chironomids by day 23 at the 100 μg a.s./L treatment was observed and possibly related to direct toxicity from thiamethoxam on larval stages. Therefore, a conservative study specific No Observed Ecological Adverse Effect Concentration (NOEAEC) is proposed to be 30 μg a.s./L. Overall, based on current concentrations of thiamethoxam detected in North American surface waters (typically <0.4 μg/L), there is low likelihood of direct or indirect effects from a pulsed exposure on primary producers, zooplankton, and macroinvertebrates, including insects, as monitored in this study. Graphical abstract: Image 1 Highlights: Thiamethoxam is detected in the surface waters of agroecosystems. A mesocosm study to understand freshwater aquatic organism responses was performed. No indications of ecologically significant direct or indirect effects at environmental concentrations. Abstract : Acute exposures to the neonicotinoid insecticide thiamethoxam at environmentally relevant concentrations do not pose a significant risk to freshwater biota.